ANALISIS PENGARUH MODEL AISAS (ATTENTION, INTEREST, SEARCH, ACTION & SHARE) TERHADAP TINGKAT LITERASI KEUANGAN SYARIAH (STUDI KASUS FOLLOWERS INSTAGRAM PERBANKAN SYARIAH) - Joni Iskandar; Mukhamad Najib; Ahmad Mukhlis Yusuf (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2020)
The Financial Services Authority (OJK) states that one of the root causes of the slow growth in the market share of Islamic banking is due to the weak literacy of Indonesian people towards sharia finance. Based on a 2016 National Literacy and Financial Inclusion survey involving 9,680 research respondents from 34 provinces in 64 cities / districts. shows that the national Islamic financial literacy rate is 8.11 percent. While on the other hand, there has been an increase in internet usage among Indonesian people. The research aims to find out how the AISAS model which consists of Attention, Interest, Search, Action and Share affects the level of literacy of Islamic banking in followers of Islamic banking in Indonesia. Research consists of three stages namely literature study. Then a field study was conducted by distributing questionnaires to 183 respondents. The analysis method used is Structural Equation Modeling (SEM) using AMOS software. The results show that (1) Attention variable has a significant and positive effect on the dependent variable, namely interest. (2) Interest variables have a significant and positive effect on the dependent variable, namely search. (3) The search variable has a significant and positive effect on the dependent variable, namely action. (4) The action variable has a significant and positive effect on the dependent variable, which is share. (5) The search variable has a significant and positive effect on the dependent variable, namely Sharia Banking Literacy. (6) The action variable has a significant and positive effect on the dependent variable, namely Sharia Banking Literacy. (7) The share variable does not have a significant effect even though it has a positive value on the dependent variable, namely Sharia Banking Literacy.